2014
DOI: 10.5194/acpd-14-21565-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aqueous phase oligomerization of methyl vinyl ketone through photooxidation – Part 2: Development of the chemical mechanism and atmospheric implications

Abstract: Abstract. We developed a chemical mechanism based on laboratory experiments that have shown efficient oligomerization from methyl vinyl ketone (MVK) in the bulk aqueous phase. Kinetic data are applied (if known) or fitted to the observed MVK decay and oligomer mass increase. The mechanism is then implemented into a multiphase box model that simulates (i) oligomer formation upon uptake of MVK from the gas phase, and (ii) SOA formation from isoprene, as a precursor of MVK and methacrolein (MACR) in the aqueous a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Currently, the aqueous-phase OH reactivity of dimers is poorly constrained. Ervens et al 25 have reported the OH reactivity of methylvinyl ketone oligomers (1 × 10 8 M −1 s −1 ), obtained by fitting experimental observations in a chemical system in which dimers formed and reacted simultaneously. The strength and novelty of this work lie in the in situ measurement of the decaying dimers that are actually extracted from α-pinene SOA.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the aqueous-phase OH reactivity of dimers is poorly constrained. Ervens et al 25 have reported the OH reactivity of methylvinyl ketone oligomers (1 × 10 8 M −1 s −1 ), obtained by fitting experimental observations in a chemical system in which dimers formed and reacted simultaneously. The strength and novelty of this work lie in the in situ measurement of the decaying dimers that are actually extracted from α-pinene SOA.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Photochemistry of dimers has not been incorporated into cloudwater chemistry models, with one exception. 25 Analysis of dimers at the molecular level is a prerequisite for understanding their chemistry, whereas for atmospheric modeling, the concept of a generalized OH reactivity 26 that represents the wide diversity of dimers is essential, given that a complete speciation of dimers is infeasible.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Very long homologous series of peaks, with mass ranging up to ∼1500 Da with three or more members and separated by the same repeating unit ("monomer") were detected in all types of experiments, as observed in previous studies of isoprene photooxidation, 15,16 isoprene ozonolysis in a smog chamber, 78 and isoprene, methacrolein, and methyl vinyl ketone bulk aqueous photooxidation. [48][49][50]79,80 Formation of such long oligomers can be explained by high concentrations of VOC precursor used in these experiments. As shown by Kourtchev et al, 41 the formation of oligomers is correlated with the initial precursor concentration (excluding a strong influence from instrumental artifacts and) confirmed by liquid chromatography mass spectrometry (LC-MS) measurements of monoterpene SOA.…”
Section: Resultsmentioning
confidence: 93%
“…In this respect, it has been shown in a previous study that dissolved O 2 inhibits radical oligomerization, 48 and water droplets in atmospheric conditions are likely to be saturated with O 2 assuming partitioning equilibrium. 49 In addition, oxidation in the condensed phase is limited by the uptake of ·OH from the gas phase. 83 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation